2011
DOI: 10.1016/s1734-1140(11)70592-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary clarithromycin, metronidazole, amoxicillin and levofloxacin resistance to Helicobacter pylori in southern Poland

Abstract: The aim of this study was to assess the primary and secondary resistance of H. pylori strains cultured from adult patients of the Małopolska region of Poland, mainly of Kraków and the surrounding areas, to antibacterial agents (amoxicillin, clarithromycin, metronidazole and levofloxacin). In total, 115 H. pylori strains were isolated, of which 90 strains originated from patients who had never been treated for H. pylori infection, while the remaining 25 were isolated from patients in whom eradication of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
5
28
0
1
Order By: Relevance
“…The risk of finding a LFX-resistant strain is in the same range after failure of a LFX-based triple therapy [18]. The present results showed that the secondary resistance of H. pylori to CLA and LFX was 73.7% and 63.2%, respectively, consistent with some studies conducted in Poland and South Korea [21,23]. After several treatment attempts, it is possible to find strains resistant to three or four antibiotics in 15% of cases [24].…”
Section: Discussionsupporting
confidence: 88%
“…The risk of finding a LFX-resistant strain is in the same range after failure of a LFX-based triple therapy [18]. The present results showed that the secondary resistance of H. pylori to CLA and LFX was 73.7% and 63.2%, respectively, consistent with some studies conducted in Poland and South Korea [21,23]. After several treatment attempts, it is possible to find strains resistant to three or four antibiotics in 15% of cases [24].…”
Section: Discussionsupporting
confidence: 88%
“…In Poland, H. pylori strains resis-tant to amoxicillin have not yet been detected, and this was confirmed by previous and current observations [12,31].…”
Section: Discussionsupporting
confidence: 87%
“…A recent report from Vietnam showed that the secondary resistance of H. pylori to clarithromycin and levofloxacin was 73,7% and 63,2%, respectively [13], this was consistent with other studies conducted in Poland and Korea [16,17]. After several treatment attempts, it was possible to find strains resistant to three, four antibiotics in 14.5% to 15.2% and 1.1% to 1.9% cases respectively, and multidrug resistance in over 56% of cases [12,13].…”
Section: H Pylori Antibiotic Resistance In Vietnamsupporting
confidence: 87%